2017
DOI: 10.1097/aap.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Assessment and Regression Rate of Bilateral Oblique Subcostal Transversus Abdominis Plane Block in Volunteers

Abstract: Bilateral oblique subcostal TAP block produces a widespread cutaneous sensory blockade with a consistent dermatomal distribution in the midabdomen for a considerable effective duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 17 publications
(19 reference statements)
1
43
0
Order By: Relevance
“…We defined a successful active sensory block as a lost or markedly reduced perception of cold. 12 Thirty minutes after ropivacaine injection, anesthesiologist who did the SAP block confirmed the loss of the dermatomal sensory. All patients underwent general anesthesia performed by attending anesthesiologists who were not involved in the study and blinded to grouping.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…We defined a successful active sensory block as a lost or markedly reduced perception of cold. 12 Thirty minutes after ropivacaine injection, anesthesiologist who did the SAP block confirmed the loss of the dermatomal sensory. All patients underwent general anesthesia performed by attending anesthesiologists who were not involved in the study and blinded to grouping.…”
Section: Methodsmentioning
confidence: 94%
“…Børglum et al reported that both testing methods yielded similar results when assessing the efficacy of transverse abdominis plane blocks. 22 Previous studies used cold stimuli to assess sensory block duration after regional anesthesia with the aim of reducing patient discomfort, 12,23 so we employed the same approach.…”
Section: Figurementioning
confidence: 99%
“…12,18,19 In a study assessing sensory loss in healthy volunteers, bilateral oblique subcostal TAP block with 20 mL of 0.375% ropivacaine effectively blocked T7-T12 dermatomes of the midabdomen. 33 In the light of this information we assumed that a volume of 30 mL should be enough for achieving adequate spread of local anesthetic mixture.…”
Section: Discussionmentioning
confidence: 99%
“…RISS block offers an advantage over transverse abdominus plane (TAP) block as the second does provide consistent coverage to lower thoracic dermatome areas. Even the subcostal TAP does not cover the lateral supraumbilical area [15]. Moreover, the clinical advantage of RISS block is that the point of injection is distant from most surgical incisions, and a catheter is unlikely to interfere with the surgical field [3].…”
Section: Discussionmentioning
confidence: 99%